Long-term effects of pancreas transplant alone on nephropathy in type 1 diabetic patients with optimal renal function - Shin, Sung; Jung, Chang Hee; Choi, Ji Yoon; Kwon, Hyun Wook; Jung, Joo Hee; Kim, Young Hoon; Han, Duck Jong (PloS one, 2018)
Limited data are available regarding optimal selection criteria for pancreas transplant alone (PTA) to minimize aggravation of diabetic nephropathy. A total of 87 type 1 diabetic patients were evaluated before and after PTA at a single center from January, 1999 to December, 2015, together with 87 matched non-transplanted type 1 diabetic subjects who were candidates for PTA to compare deterioration of native kidney function. A total of 163 patients (79 in the transplanted group and 84 in the nontransplanted group) were finally enrolled after excluding nine patients with estimated glomerular filtration rate less than 60 mL/min/1.73 m2 and two patients with moderate proteinuria (≥ 1.5 g/day). A total of seven recipients (8.9%) had end-stage renal disease post-transplant whereas only one patient (1.2%) developed end-stage renal disease in the nontransplanted group during their follow-up period (median 12.0, range 6-96 months) (p = 0.03). Furthermore, a composite of severe renal dysfunction and end-stage renal disease (31.6% vs 2.4%) was significantly higher in the transplanted group (p < 0.001). Multivariate Cox regression analysis revealed that a higher level of tacrolimus at six months post-transplant (HR = 1.648, CI = 1.140-2.385, p = 0.008) was the only significant factor associated with end-stage renal disease. There is a considerable risk for deterioration of renal function in PTA recipients post-transplant compared with non-transplant diabetic patients. With rather strict selection criteria such as preoperative proteinuria and estimated glomerular filtration rate, PTA should be considered in diabetic patients to minimize post-transplant aggravation of diabetic nephropathy.